2019
DOI: 10.3390/coatings9120851
|View full text |Cite
|
Sign up to set email alerts
|

Improving Thickness Uniformity of Mo/Si Multilayers on Curved Spherical Substrates by a Masking Technique

Abstract: In this work, a masking technique was used to improve the thickness uniformity of a Mo/Si multilayer deposited on a curved spherical mirror by direct current (DC) magnetron sputtering with planetary rotation stages. The clear aperture of the mirror was 125 mm with a radius of curvature equal to 143.82 mm. Two different shadow masks were prepared; one was flat and the other was oblique. When using the flat mask, the non-uniformity considerably increased owing to the relatively large gap between the mask and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…The nonuniformity of film thickness is a significant criterion for assessing film quality, as it can directly influence the usable size, productive yield, and overall production cost. In industrial production, film thickness nonuniformity is often required to be lower than 3∼5%, and some processes even have stricter requirements. For example, in order to achieve constant optical properties on the optical element surfaces of high-resolution microscopes, telescopes, and other related optical systems, depositing uniform coatings with better than 0.8% nonuniformity was normally demanded . In addition, film thickness nonuniformity can impact the film’s performance, such as the photovoltaic property and optical constants .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonuniformity of film thickness is a significant criterion for assessing film quality, as it can directly influence the usable size, productive yield, and overall production cost. In industrial production, film thickness nonuniformity is often required to be lower than 3∼5%, and some processes even have stricter requirements. For example, in order to achieve constant optical properties on the optical element surfaces of high-resolution microscopes, telescopes, and other related optical systems, depositing uniform coatings with better than 0.8% nonuniformity was normally demanded . In addition, film thickness nonuniformity can impact the film’s performance, such as the photovoltaic property and optical constants .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in order to achieve constant optical properties on the optical element surfaces of high-resolution microscopes, telescopes, and other related optical systems, depositing uniform coatings with better than 0.8% nonuniformity was normally demanded. 15 In addition, film thickness nonuniformity can impact the film's performance, such as the photovoltaic property 16 and optical constants. 17 Badgujar et al reported that to achieve high photoelectric conversion efficiency in copper indium gallium selenide (CIGS) thin-film solar cells, uniform and crystalline Mo(110) thin films were desired as a back contact.…”
Section: Introductionmentioning
confidence: 99%
“…IBF provides both high accuracy and high efficiency, and a figure error of 0.5 µrad (root mean square (RMS)) has been widely realized [8]. The addition methods include differential deposition [9][10][11][12][13] and profile coating [14][15][16][17][18][19] based on modern physical deposition techniques. These are also high-precision and high-efficiency correction techniques, and expensive substrates can be reused to create different profiles since the added correction layer can be removed with different methods [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The smallest RMS deviation between the deposited profile and the designed ellipse was below 0.41 nm [15]. Coating methods are easily implemented using standard coating machines, so there are gradually more people working on these methods [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation